Enhancing the endogenous potential of agricultural landscapes. Strategies and projects for a inland rural region of Sicily. - Prestia, Gerlandina; Scavone, Valeria (Springer, 2018)
This paper focuses on the potential of the rural landscape of Sicily, the largest island in the Mediterranean Sea, taking into particular account the critical need to deal with the problem of depopulation of the small inner areas by leveraging the integrated exploitation of local resources. The rural landscape is considered to be capable of playing an essential role in many fields: ecology, production, culture and tourism. In this regard, guidelines are set by the Sustainable Development Goals of the United Nations, the EU guidelines and the experience from Italy s Rural Development Plans, the latter of which aim at achieving the much sought-after multi-functionality of agriculture. This study has been conducted in our particular moment in history, when new attention is being drawn to the potential of rural landscape due to its fragility, the crisis of traditional production systems and the changes caused by urbanization, which have had irreversible effects on many rural areas, based on traditional agriculture, and on ecosystem services. Keeping this goal in mind, the Sicilian case study should be considered as a sort of test bench where the validity of the abovementioned considerations can be tested. The area Agrigento-Caltanissetta-Enna in mid-southeastern Sicily is an area composed of sixteen municipalities in the three (ex) regional provinces of Agrigento, Caltanissetta and Enna, which, from the coast facing Africa (characterised by major cultural sites UNESCO Heritage) stretches to the heart of inner Sicily along the grey line composed of trunk road S.S. 122. The rural landscape that characterizes this area is the result of a complex process of interactions between various natural and anthropic factors that often conflict with each other and define the identity of the landscape itself and its dynamic and economic processes. The area treated in this paper has been analyzed to highlight its particular features, thus proposing a landscape project called NetWalk. This paper employs several different strategies needed to develop the NetWalk project, each with its own specific aims: opportunities arising from the agreement that allows the Italian state-property agency to sell its roadman s houses, and from the downgrading of trunk road 122, which might become a slow path through this region while connecting with important areas and resources; the return to walking paths (promoted by the Italian Ministry of Cultural Heritage and Activities and Tourism in 2016), with the purpose of creating a green network made up of slow paths, of previously abandoned buildings that should be renovated and adapted for new uses, of highly-valued (even though they are currently considered of minor importance) rural landscapes, and of intangible assets which thus become tangible; the Italian Rural Development Plans, which involve a strategic change in the role of agriculture, which should be linked to the concept of multi-functionality in many different ways: from farming for energy production, to the protection of rural landscapes in terms of tourism services, to education and social services; the many food quality certifications granted to many typical Sicilian products. All these activities, when properly carried out, will create a bio-region in the area covered by the project. The inhabitants of this region will share a sense of belonging, identity and collective memory.
Keywords: Ländlicher Raum; Abwanderung; Landflucht; Regionalentwicklung; Landwirtschaftsentwicklung; Landschaftskonzept; Multifunktionalität; Entwicklungspotenzial; Regionalplanung